INTELLIGENT SCREENING: PREDICTIVE VALIDATION OF CHATBOT USING ARTIFICIAL INTELLIGENCE TO PRE-SCREEN PATIENTS FOR UNIVERSITY CLINIC (REMUNOM, 2024)
The Faculty of Dentistry of the Federal University of Pará presents obstacles in the screening patients. Objective: to carry out the predictive validation of a chatbot developed to pre-screen patients. Methods: this is a quantitative cross-sectional study to compare the data reported by humans to the chatbot with the clinical examination. Thirty individuals made up the sample. Fisher's Exact, accuracy and Cohen's Kappa tests were applied. Results: The use of cell phones for scheduling appointments was statistically different (p=0.025) among those who use it to read news. There was agreement above 80% between the measurement of the chatbot and the clinical examination; perfect reproducibility (Kappa>0.800, p